2021
DOI: 10.1029/2020je006512
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Geometry and Emplacement Conditions of a Giant Dike System in Elysium Fossae, Mars

Abstract: Mars is a planet with extensive volcanism. The two volcanic provinces of Tharsis and Elysium show multitude of large volcanoes, smaller shield edifices, unrooted cones, lava flows, and volcanic plains of a wide range of ages (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 147 publications
1
31
0
Order By: Relevance
“…On the other hand, the lateral propagation of the system toward the east implies that the seismicity could be also located at depth near the propagating dike tips (Green et al, 2015;Rubin & Gillard, 1998;Sigmundsson et al, 2015). Indeed, Rivas-Dorado et al (2021) have shown that Martian conditions are favorable to develop giant dike systems (e.g., Elysium Fossae) that could reach much greater depths (15-20 km).…”
Section: Regional and Local Stress Concentrations: Constraints On Marsquake Locations Recorded By The Insight Missionmentioning
confidence: 99%
“…On the other hand, the lateral propagation of the system toward the east implies that the seismicity could be also located at depth near the propagating dike tips (Green et al, 2015;Rubin & Gillard, 1998;Sigmundsson et al, 2015). Indeed, Rivas-Dorado et al (2021) have shown that Martian conditions are favorable to develop giant dike systems (e.g., Elysium Fossae) that could reach much greater depths (15-20 km).…”
Section: Regional and Local Stress Concentrations: Constraints On Marsquake Locations Recorded By The Insight Missionmentioning
confidence: 99%
“…This would help with the undertaking of a quantitative back restoration of structures and related processes and thus help to improve current geophysical and geodetic models for eruption forecasts. In addition, for the growing field of planetary volcanology with surface imagery as the main data source, we need a solid understanding of related magma transport in the subsurface to be able to interpret extra-terrestrial processes e.g., [109]. the Sosa family and Rubén Castillo.…”
mentioning
confidence: 99%
“…1A). It is widely acknowledged that this model-predicted value for fracture toughness is much larger than the expected values for the host rock (Rivalta et al, 2015;Cruden et al, 2017), with model results typically in the region of 𝐾 𝐼𝑐 = 300 − 3000 𝑀𝑃𝑎 √𝑚 on Earth (Schultz et al, 2008), with estimates up to 𝐾 𝐼𝑐 = 15,000 𝑀𝑃𝑎 √𝑚 on Mars (Rivas-Dorado et al, 2021); these predictions are compared to ~1 𝑀𝑃𝑎√𝑚 in nature (Atkinson, 1984). To appreciate how unphysical these calculated values are, the fracture toughness of all classes of material are shown in Figure 1C, where 𝛼 ≈ 10 −5 √𝑚 for technical ceramics including glass, and 𝛼 ≈ 10 −4 √𝑚 for building materials such as concrete and brick, with the very highest values of 𝛼 ≈ 10 −3 √𝑚 for high-performance structural materials such as metal alloys.…”
Section: Introductionmentioning
confidence: 77%